Serum Vitamin D Levels in Patients with Type 2 Diabetes Mellitus with and without Peripheral Neuropathy - Tammineni Roja; Siba Prasad Dalai; Gyanendra Sathua Mahapatra; Samir Sahu; Jonnalagadda Vihari; Lohitha Bhavani Jasthi (Dr. Annil Mahajan, 2024)
Introduction: Serum vitamin D levels has been hypothesized to influence the progress of diabetes and its various complications. The role of Vitamin D in diabetic peripheral neuropathy have been debated. Aim of the Study: This study was conducted to compare serum vitamin D levels in patients with diabetic peripheral neuropathy and patients with type 2 diabetes mellitus without neuropathy, as well as to assess any possible association between serum vitamin D levels and severity of diabetic peripheral neuropathy. Subjects and Methods: This is a case-control study involving 100 cases and 100 controls in which serum vitamin D levels and severity of neuropathy were assessed using Vibration perception threshold (VPT). Results: The levels of Vitamin D were significantly lower in cases (patients with diabetes with peripheral neuropathy) compared to controls (patients with diabetes but without peripheral neuropathy). The mean serum levels of 25(OH)D in cases was 14.1± 3.2 ng/ml and in controls was 22.3 ± 3.8 ng/ml which was statistically significant (p value < 0.001). The mean serum vitamin D levels in cases with mild neuropathy (VPT 20-24 mV) was 16.8 ± 3.2 ng/ml, moderate neuropathy (VPT 25-39 mV) was 14.5 ± 1.4 ng/ml, and in those with severe neuropathy (VPT >39 mV) was 11.6 ± 2.1 ng/ml (p=0.004). A significant negative correlation was observed between Serum Vitamin D levels and VPT (r = -0.65, p<0.001). Conclusion: Vitamin D levels were significantly lower among patients of diabetes mellitus with neuropathy as compared to patients of diabetes without any evidence of underlying neuropathy. Vitamin D levels also varied significantly with severity of diabetic peripheral neuropathy. Vitamin D might be used as a valuable marker for prognostication of cases of diabetic peripheral neuropathy and can be advocated as a special test once the patient develops minimal sign and symptoms of peripheral neuropathy. Lifestyle changes and medications to improve Vitamin D levels should be advocated irrespective of glycaemic control to reduce the symptoms and incidence of microvascular complications such as diabetic peripheral neuropathy.